Are energy transitions an opportunity or risk to climate security? - Bößner, Stefan; Taylor, Alice (2021)
COP26 cemented commitments from countries to do more to mitigate the climate crisis. Increasingly galvanised climate protests and serious calls from scientists formed a pre-cursor to the conference, where countries gathered to negotiate plans to limit global warming to 1.5C. One of the most polluting sectors is energy, and so was the focus of many of the discussions. Besides its importance for the global economy, energy can play a role in driving global conflicts. However, the potential repercussions of energy transitions have remained relatively under explored, both at the conference, and in public and academic discourse more generally.